2021
DOI: 10.1002/pmic.202100060
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐activated complexation of α‐synuclein with three diverse β‐barrel channels: VDAC, MspA, and α‐hemolysin

Abstract: Voltage-activated complexation is the process by which a transmembrane potential drives complex formation between a membrane-embedded channel and a soluble or membrane-peripheral target protein. Metabolite and calcium flux across the mitochondrial outer membrane was shown to be regulated by voltage-activated complexation of the voltage-dependent anion channel (VDAC) and either dimeric tubulin or αsynuclein (αSyn). However, the roles played by VDAC's characteristic attributes-its anion selectivity and voltage g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…where R acc is the access resistance given in eq 1. 7, and R ws is the intrinsic diffusion resistance of the channel with the blocking cylinder given by…”
Section: Blocker Of Abruptly Changing Radius (Blocking Cylinder)mentioning
confidence: 99%
See 1 more Smart Citation
“…where R acc is the access resistance given in eq 1. 7, and R ws is the intrinsic diffusion resistance of the channel with the blocking cylinder given by…”
Section: Blocker Of Abruptly Changing Radius (Blocking Cylinder)mentioning
confidence: 99%
“…It is emerging as a powerful tool for detection and analysis of analytes of diverse origin at a single molecule level. A substantial progress has already been achieved in DNA and protein sequencing, investigations of protein-protein interactions, , and studies in single-molecule enzymology and post-translational protein modifications. Nanopore sensing is based on the fact that upon their passage through a nanopore different analyte molecules reduce, that is, partially block, the nanopore current to a different extent, thus allowing to gauge their physico-chemical properties. Though there is a well-appreciated progress in quantitative understanding of the amplitude and time characteristics of the analyte-induced transients in nanopore current, a reliable theoretical background of this phenomenon is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have modelled polymers in the nanopore environment as they interact with a collection of free energy barriers to transport (i.e., capture, partitioning, and escape) [9–13] and this can help researchers better understand optimization strategies for designing better sensors. Hoogerheide and colleagues [14] extend this theme with a study on voltage dependent transport of α‐synuclein and a variety of nanochannels. This study models the free energy profile of the α‐synuclein peptides, which yields numerous conclusions about the nature of the polymer–pore interactions.…”
Section: Introductionmentioning
confidence: 97%
“…17 It was shown that in this signaling mechanism the disordered tail is trapped by the channel whereas the rest of the protein body – its structured part – serves as a membrane-bound anchor. 18…”
Section: Introductionmentioning
confidence: 99%
“…17 It was shown that in this signaling mechanism the disordered tail is trapped by the channel whereas the rest of the protein body -its structured part -serves as a membranebound anchor. 18 In developing the theory, two questions naturally arise: (1) how to choose the hemisphere radius and ( 2) what is the range of applicability of our approach that ignores the angular dependence? Our choice of the hemisphere radius is discussed in the next Section 2.…”
Section: Introductionmentioning
confidence: 99%